1998
DOI: 10.1300/j013v27n01_13
|View full text |Cite
|
Sign up to set email alerts
|

Streets, Drugs, and the Economy of Sex in the Age of AIDS

Abstract: Drug addicted women whose economic and social base is urban streets face limited options for income generation and multiple dangers of predation, assault, arrest, and illness. Exchanging sex for money or drugs offers one important source of income in this context. Yet the legal, social, and safety risks associated with these exchanges reduce the likelihood of regular safer sex practices during these encounters, thereby increasing the risk of HIV infection. Such conditions lead women engaged in sexual exchanges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 30 publications
1
40
1
1
Order By: Relevance
“…These include their own or their partner's dislike of male condoms or discomfort using them, desire for intimacy signified by non-use of condoms, and the need for more income. These are typical reasons for unprotected sex found in numerous other studies (Bowleg, Lucas, & Tschann, 2004;Lau et al, 2002;Pulerwitz, Amaro, DeJong, Gortmaker, & Rudd, 2002;Weeks, Grier, Romero-Daza, Puglisi-Vasquez, & Singer, 1998). Women's inconsistent ability or desire to use male condoms with their paying or primary partners results in much exposure to risk.…”
Section: Discussionsupporting
confidence: 56%
“…These include their own or their partner's dislike of male condoms or discomfort using them, desire for intimacy signified by non-use of condoms, and the need for more income. These are typical reasons for unprotected sex found in numerous other studies (Bowleg, Lucas, & Tschann, 2004;Lau et al, 2002;Pulerwitz, Amaro, DeJong, Gortmaker, & Rudd, 2002;Weeks, Grier, Romero-Daza, Puglisi-Vasquez, & Singer, 1998). Women's inconsistent ability or desire to use male condoms with their paying or primary partners results in much exposure to risk.…”
Section: Discussionsupporting
confidence: 56%
“…It followed that interventions, to succeed, must intervene at more than one level if they were to achieve lasting success. Both sex work and substance abuse may be viewed from an economic perspective as phenomena representing rational decisions, made by individuals operating within severely constrained circumstances (Goldstein, 1979;Goldman, 1981;Romero-Daza, Weeks & Singer, 1998;Hanson, Lopez-Iftikhar, Alegria et al, 2002;Maher, 1996;Maher & Daly 1996;Bretteville-Jensen & Sutton, 1996). Research has shown that women who engage in street sex work are more likely to have suffered from child sexual abuse (Widom & Kuhns, 1996;McClanahan et al, 1999), to demonstrate signs of psychological distress (Young, Boyd and Hubbell 2000), and to experience stigmatization and poor overall health (Baker, Wilson, & Winebarger, 2004;Jeal & Salisbury, 2004).…”
Section: Finding Funding and Developing A Theoretical Approachmentioning
confidence: 99%
“…For example, exchanging sex for money may be a way for women to obtain economic resources for their drug addiction (Weeks et al 1998). Cocaine and other stimulant injection may increase sexual risk, probably due to increased sexual activity and more partners (Maranda et al 2004;Somlai et al 2003).…”
Section: Introductionmentioning
confidence: 99%